Efficacy and Safety of Terbinafine Compared with Other Antifungal Agents in Dermatophytosis: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Ida Ayu Uttari Priyadarshini; Putu Tiara Mas Pracinti Ariesta Putri; Putu K. Helsayani (Explorer Front, 2026)
Background: Dermatophytosis is a frequent superficial fungal infection that causes significant morbidity and is increasingly associated with treatment failure. Terbinafine is frequently used as a first-line therapy; however, its relative efficacy compared with other antifungal agents remains inconsistent. This study aimed to assess the effectiveness and safety of Terbinafine compared to other antifungal agents in patients with dermatophytosis. Methods: A systematic review and meta-analysis of the past 20 years was conducted following PRISMA 2020 guidelines. The databases used were PubMed, the Cochrane Library, and ScienceDirect. The outcomes assessed included overall cure, mycological cure, clinical cure, treatment failure, and adverse events. Random-effects models calculated risk ratios (RRs) and 95% confidence intervals (CIs). Results: Thirteen RCTs were analyzed. No notable differences were found between Terbinafine and other antifungal agents in overall cure (RR: 0.87; 95% CI: 0.74–1.02), mycological cure (RR: 1.11; 95% CI: 0.89–1.38), or clinical cure (RR: 1.06; 95% CI: 0.96–1.16). However, Terbinafine was associated with a higher risk of treatment failure (RR: 6.22; 95% CI: 1.50–25.80). Subgroup analyses indicated Terbinafine was less effective for tinea corporis and tinea cruris, but more effective for tinea capitis. There were no significant differences in adverse events between the groups. Conclusion: Terbinafine demonstrated efficacy comparable to that of other antifungal agents, but it may increase the risk of treatment failure under certain conditions. Its effectiveness appears to be context-dependent and influenced by the type of dermatophytosis and the causative pathogen.